Two centuries of solidarity : German, Belgian, and Dutch social health care insurance 1770-2008 - Companje, K. P. (Karel-Peter), 1955-; Veraghtert, Karel, 1944-; Widdershoven, B. E. M. (Brigitte E. M.) (HiZ-series history of healthcare insurance, 2009)
Today, health insurance is a key component in the system of social security in most European Union countries. In many of these countries, modern health-insurance funds and healthcare insurers play an essential role in implementing the public health-insurance system. Many of these health-insurance funds have a long and fascinating history, of which clear traces can be seen today in the organisation and structure of health insurance, as well as health-insurance funds and insurers. In Two centuries of solidarity, the authors compare the systems of health insurance, health-insurance funds and health.